Injury prevention strategies for the neck, back and shoulders - O'Brien, Teri (Monterey, CA : Healthy Learning Videos, 1999)
Explain about the primary musculoskeletal problem area and demonstrates a series of exercise for treating and preventing each painful condition
Keywords: Shoulder pain -- Prevention; Neck pain -- Prevention; Backache -- Prevention